2019
DOI: 10.1016/j.jamda.2019.01.152
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of an Alternative Diagnostic Method for Sarcopenia Using Thickness and Echo Intensity of Lower Leg Muscles in Older Males

Abstract: JAMDA jo u rn a l h o m e p a g e : w w w. j a m d a. c o m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 37 publications
2
50
1
Order By: Relevance
“…The current study also clearly showed that the muscle quality was consistently associated with the EI of the lower leg muscles and QFM in older adults (Table 4). Our previous study demonstrated that the ultrasonographic assessment of the lower leg muscles, notably the TA, might be a convenient approach for detecting sarcopenia 42 . Ikezoe et al reported that the MT of the TA, as well as the thigh muscle, significantly decreased in a year in an older Japanese female population 43 .…”
Section: Discussionmentioning
confidence: 94%
“…The current study also clearly showed that the muscle quality was consistently associated with the EI of the lower leg muscles and QFM in older adults (Table 4). Our previous study demonstrated that the ultrasonographic assessment of the lower leg muscles, notably the TA, might be a convenient approach for detecting sarcopenia 42 . Ikezoe et al reported that the MT of the TA, as well as the thigh muscle, significantly decreased in a year in an older Japanese female population 43 .…”
Section: Discussionmentioning
confidence: 94%
“…Using a 13-MHz GE Healthcare LOGIQe and a 13-MHz FujiFilm SonoSite M-Turbo probe and diagnostic ultrasonography equipment (Wuxi, China, and Bothell, Washington, USA, respectively), measurements of muscle thickness (MT) and echo intensity of the anterior rectus muscle and vastus medialis muscle will be obtained. 55 A strong correlation between conventional radiological Open access measurements (by MRI or CT) and ultrasound measurements of MT has been previously demonstrated. 56…”
Section: Muscle Ultrasoundmentioning
confidence: 79%
“…In these instances, it may be more appropriate to perform multiple‐linear regression, with both adipose tissue thickness and echo intensity as independent variables associated with glucose homeostasis. Yet, despite these potential limitations, several publications have observed associations between uncorrected echo intensity and muscle strength, 15,30 function, 16,31 and metabolism, 32 indicating that it may still be a valid metric of muscle composition, but future work exploring its correction is needed to better understand the ideal approaches for its measurement and analysis.…”
Section: Discussionmentioning
confidence: 99%